Synthesis and structures of the triple-decker type complexes CpCo([mu]1,3-C3B2Me5)MX2L (M = Rh and Ir; X = Cl and Br; L = Me2SO and PPh3) - Romanov, Alexander S.; Siebert, Walter (Journal of organometallic chemistry, 2012)
The dimeric triple-decker type halides [CpCo(μ-1,3-C3B2Me5)MX2]2 (M = Rh, X = Cl, 1; M = Ir, X = Cl, 2; M = Rh, X = Br, 3; M = Ir, X = Br, 4) react with Me2SO and PPh3 giving adducts CpCo(μ-1,3-C3B2Me5)M(L)X2 (5-12). The Me2SO ligand is S-bonded to the metal atom in the solid state, while in acetone it is O-bonded. Structures of 5-12 were confirmed by X-ray diffraction.